THE EFFECT OF JOB ROTATION AND TRAINING ON EMPLOYEE PERFORMANCE IN PT. PEGADAIAN (PERSERO) MANADO - Jocom, Jessica; Lambey, Linda; Pandowo, Merinda (Universitas Sam Ratulangi, 2017)
Â ABSTRACT: Nowdays, every organization definitely strive to improving its employee performance. Organization needs to make their employees work in the maximum of their capabilities. The objective of this research is to analyze the effect of job rotation and training on employee performance. The data was analyze quantitatively with multiple regression analysis method. This research is causal type of research which uses primary data obtained through questionnaires. The respondents of this research are the permanent employees in PT. Pegadaian (Persero) Manado with sample size as many as 100 respondents. The result of this study shows that Job Rotation has no significant influence on employee performance and Training has positive significant influence on employee performance. PT. Pegadaian (Persero) Manado should be more concerned to manage job rotation program, to prevent the dissatifaction of employee. And should keep up the training program in order to maintain employee performance to the better level. KEYWORDS: Job Rotation, Training, Employee Performance